On solution of Fredholm integrodifferential equations using composite Chebyshev finite difference method - Atabakan, Zohreh Pashazadeh; Nasab, Aliasghar Kazemi; Kilicman, Adem (Hindawi Publishing Corporation, 2013)
A new numerical method is introduced for solving linear Fredholm integrodifferential equations which is based on a hybrid of block-pulse functions and Chebyshev polynomials using the well-known Chebyshev-Gauss-Lobatto collocation points. Composite Chebyshev finite difference method is indeed an extension of the Chebyshev finite difference method and can be considered as a nonuniform finite difference scheme. The main advantage of the proposed method is reducing the given problem to a set of algebraic equations. Some examples are given to approve the efficiency and the accuracy of the proposed method.